Mathematical model for calculating the economic efficiency of the process of manufacturing defect-free sections for shape-resistant furniture panels - Podibka, T.I. (Forestry, Forest, Paper and Woodworking Industry, 2022)
A mathematical model was developed for calculating the economic efficiency of the EEFB process of obtaining lamellas from monolithic and jointed lamellas from defect-free pieces of wood residues (WR) and primary wood (PW) for furniture panels of a given dimensional stability, the use of which will make it possible to forecast the prospects for the development of the enterprise, to efficiently and quickly determine the estimate of the production cost price of furniture boards made of defect-free areas of pine and beech lamellas. It is calculated that the final EEFB of using WR category WR -0 in comparison with PW I grade for the production of high-quality blanks from beech wood is 207.44%, and from pine wood is 184.921% and stimulates the introduction of resource-saving production technologies, in particular furniture panels. It has been established that, as demonstrated by the results of comparative studies on the estimation of the production cost of traditional FB with PW and FB with WR, it is possible to obtain financial and ecological and economic benefits when using WR. The main benefit of the manufacturer is the reduction of material costs for the production of MH with WR in comparison with traditional FB with PW. Thus, with the construction of furniture boards 50% from PW and 50% from WR, the income from the sale of furniture boards for the volumes of 257.91 thousand m3 for pine and 32.73 thousand m3 for beech will be: common pine – 5841.49 million hryvnias ; ordinary beech – 1018.74. million hryvnias, and accordingly – savings will amount to 1741.00 million hryvnias; and UAH 356.00 million. And for the constructions of furniture panels 100% from WR, the income from the sale of furniture panels for these volumes will be: common pine – 4100.49 million hryvnias; ordinary beech – 662.73 million hryvnias, and accordingly – savings will amount to 3482.00 million hryvnias; and UAH 712.00 million. Thus, the calculations show that the price reduction of FB with WR is from 22.96% to 25.89% with the 50%/50% design, from 45.92% to 51.79% with 100% use of WR. It is calculated that for the construction of furniture panels 50% from PW and 50% from WR, the cost of 1 m2 will be: ordinary pine – UAH 539.27; ordinary beech – UAH 741.04; for the construction of furniture panels 100% from WR, the cost of 1 m2 will be: common pine – UAH 321.45; common beech (forest) – UAH 517.93.